Cloning, characterization, and enzymatic identification of a new tryptophan decarboxylase from Ophiorrhiza pumila. (25th May 2020) - You, Dawei; Feng, Yue; Wang, Can; Sun, Chengtao; Wang, Yao; Zhao, Degang; Kai, Guoyin
Abstract: Tryptophan decarboxylase (TDC, EC 4.1.1.28) catalyzes tryptophan decarboxylation to form tryptamine through the cofactor pyridoxal‐5′‐phosphate (PLP), a crucial stage in the production of the terpenoid indole alkaloids like camptothecin (CPT). A new gene encoding TDC was identified from the CPT‐producing plant Ophiorrhiza pumila by transcriptome analysis, termed OpTDC2. It contained a 1, 536 bp open reading frame that encodes a 511 amino acid protein with a molecular mass of 57.01 kDa and an isoelectric point of 6.39. Multiple sequence alignment and phylogenetic tree analysis showed the closest similarity (85%) with the TDC from Mitragyna speciosa . Moreover, the highest expression of OpTDC2 was observed in the O. pumila root. To achieve high‐efficiency expression of OpTDC2 in Escherichia coli, we fused the TF tag onto the N‐terminal of the OpTDC2. Optimum enzymatic activity was observed at 45 °C, pH 8 and cofactor concentration of 0.1 mM. The catalytic reaction was strongly inhibited by metal ions of Cu 2+, Zn 2+, and Fe 2+ . The l ‐tryptophan was particularly catalyzed compared with d ‐tryptophan. Besides, the K m and k cat of the OpTDC2 were 1.08 mM and 0.78 Sec −1, respectively. The results provided information on new functional OpTDC2 that might be used in synthetic biology for the enhanced biosynthesis of CPT in O. pumila . Abstract :